Mapping the literature of integrated marketing communications: A scientometric analysis using CiteSpace - Lingling Wu; Yuriy Danko; Fuli Chen; Xuefeng Yao; Fenghe Zhang (Innovative Marketing)
Integrated marketing communication (IMC) is an effective marketing practice in the age of social media. IMC builds customer relationships and enhances brand value by integrating information from multiple channels and strengthening user interaction. The purpose of this study is to present the development process, current hotspots, and future trends of IMC research. Moreover, it explores the characteristics and patterns of IMC research. First, this paper shows the annual literature volume, leading countries, journals, and authors in IMC research through bibliometrics. Then, five hot research topics are identified through keyword co-occurrence analysis, namely IMC theory and models, brand communication, media research, customer research, and marketing strategy. From 1991 to 2020, IMC research is divided into five phases, each of which is related to the enhancement of user interaction. Future IMC research will continue to be user-centered, and IMC research will continue with social media and branding, as well as research on other topics that can further enhance user interactions. This paper also finds that the characteristics of the concept of IMC itself lead to a constant renewal of its connotations, which is one of the reasons why scholars cannot reach a consensus on the concept of IMC. AcknowledgmentsWe thank Associate Professor Zhenkun Cui of Henan Institute of Science and Technology for his valuable comments during the writing and revision of this paper. The following research projects supported this study: (1) Henan Provincial University Humanities and Social Sciences Research Project No.2022-ZDJH-0099; (2) Henan Provincial University Humanities and Social Sciences Research Project No.2022-ZZJH-158; (3) Henan Province Social Science Planning Project No. 2021BZZ004; and (4) Xinxiang Social Science Federation Research Project No. 2021-167.